After Death, Death: The Mechanics of Longing in Henry Carrington's «The Siren» - Teodorski, Marko (Amaltea. Revista de Mitocrítica, 2019)
This essay deals with the mechanics of longing in a late Victorian siren poem by Henry Carrington, The Siren. Although Victorian literature was teeming with short stories, poems and novels on sirens, this genre, that builds upon and reverses Homeric siren tradition, remains neglected in literary discussions. With the translation of The Little Mermaid into English in 1872, the image of a "longing siren" was born. No longer were these the stories of Odysseus who had survived the siren song: now they were about the sirens’ own sorrows, griefs and desires. Sirens became profoundly human – they became desiring subjects themselves.